Impaired Mitochondrial Fusion and Oxidative Phosphorylation Triggered by High Glucose Is Mediated by Tom22 in Endothelial Cells. (19th May 2019) - Zeng, Yi; Pan, Qi; Wang, Xiaoxia; Li, Dongxiao; Lin, Yajun; Man, Fuli; Xiao, Fei; Guo, Lixin
Abstract : Much evidence demonstrates that mitochondrial dysfunction plays a crucial role in the pathogenesis of vascular complications of diabetes. However, the signaling pathways through which hyperglycemia leads to mitochondrial dysfunction of endothelial cells are not fully understood. Here, we treated human umbilical vein endothelial cells (HUVECs) with high glucose and examined the role of translocase of mitochondrial outer membrane (Tom) 22 on mitochondrial dynamics and cellular function. Impaired Tom22 expression and protein expression of oxidative phosphorylation (OXPHOS) as well as decreased mitochondrial fusion were observed in HUVECs treated with high glucose. The deletion of Tom22 resulted in reduced mitochondrial fusion and ATP production and increased apoptosis in HUVECs. The overexpression of Tom22 restored the balance of mitochondrial dynamics and OXPHOS disrupted by high glucose. Importantly, we found that Tom22 modulates mitochondrial dynamics and OXPHOS by interacting with mitofusin (Mfn) 1. Taken together, our findings demonstrate for the first time that Tom22 is a novel regulator of both mitochondrial dynamics and bioenergetic function and contributes to cell survival following high-glucose exposure.